Determination of Post Striga Attachment Resistance in Selected Resistant Sorghum Lines in Kenya - Manene, Diana W.; Njoka, Fredrick M. (International Knowledge Press, 2017)
Breeding for Striga resistance in sorghum and other cereals is recognized as the most sustainable control measure, however there is a lack of cereal germplasm that exhibit post attachment to Striga that limits this noble approach. This study evaluated post attachment resistance levels of four Striga resistant sorghum (SRS) lines against four ecotypes of Striga from Kenya and Tanzania. Sorghum seeds were grown in rhizotrons (root observation chambers) and the seedlings were inoculated with pre-germinated Striga seeds and on emergence the attached parasites were harvested from the roots of sorghum and scored for the number of attachments, length and dry biomass. There was a significant difference in the biomass and average length of attached Striga seedlings among the three Kenyan ecotypes on all sorghum lines. The phenotype of a resistance mechanism was characterized by the inability of the parasite to penetrate host endodermis, necrosis and the browning and death of attached Striga seedlings. SRS 1208/2 had very high post- attachment resistance to the S. hermonthica ecotypes used in this study, SRS 2408 and SRS 2208 exhibited intermediate resistance while SRS 3308/5 had low resistance. The difference in biomass, number and length of attached Striga seedlings upon infection clearly indicated genetic variability for Striga resistance in the selected lines. Among the four sorghum lines studied, cultivar SRS 1208/2 was the most promising source of resistance to obligate root parasite S. hermonthica and can be recommended for future use in sorghum breeding programs in East Africa.
Keywords: Striga; ecotypes; resistance; selection; rhizotron